Blood Pressure in Patients Obstructive Sleep Apnea and Resistant Hypertension with Continuous Positive Airway Pressure (CPAP) Therapy: A Systematic Review and Meta-Analysis - Rivania, Mutiara Rizqia; Pikir, Budi Sustyo; Lestari, Pudji; Islamiyah, Wardah Rahmatul (Universitas Airlangga, 2024)
Highlight: CPAP therapy is a medical treatment for individuals suffering from OSA, a condition that is frequently linked to cardiovascular disease and resistant hypertension. Five studies clearly showed that combining CPAP therapy with standard medications had a big effect on the blood pressure of patients with both obstructive sleep apnea (OSA) and resistant hypertension. Administering CPAP in conjunction with standard treatment, as per guidelines, has demonstrated the capability to lower both daytime and nighttime blood pressure in individuals affected by OSA and resistant hypertension. ABSTRACT Introduction: Obstructive sleep apnea (OSA) is an upper respiratory tract disorder that is often associated with cardiovascular diseases, one of which is resistant hypertension (RH). On the other side, Continuous Positive Airway Pressure (CPAP) is a medical treatment that is often used for patients with OSA and RH. Objective: This meta-analysis aimed to determine the effectiveness of CPAP in patients with OSA and resistant hypertension by measuring systolic and diastolic blood pressure at diurnal, nocturnal, and 24 hours. Methods: We conducted a systematic review using a PRISMA flowchart, utilizing sources such as PubMed, Scopus, Science Direct, and ClinicalTrials.gov with MeSH. We then reviewed these sources for quality studies using RoB2, and analyzed the data using the Revman website version. 5.4.Results: The five studies included in the analysis found that CPAP, while maintaining conventional drugs, significantly affected the blood pressure of patients with OSA and RH. The significant results were made clearer by obtaining data for nocturnal SBP pressure, mean -3.89 mmHg (95% CI: -7.03 to -0.76) with a p-value < 0.02, and then nocturnal DBP obtained a mean of -2.34 mmHg (95% CI: -4.70 to 0.02) with a p-value < 0.05. Meanwhile, the 24-hour results for SBP obtained a mean of -2.97 mmHg (95% CI: -5.88 to -0.06) with a p-value < 0.05, and the 24-hour results for DBP obtained a mean of -2.39 mmHg (95% CI: -4.62 to -0.16) with a p-value < 0.04. Conclusion: CPAP, while maintaining conventional treatment according to indications, can reduce 24-hour and nocturnal blood pressure in patients with OSA and resistant hypertension.